Sosialisasi Komunikasi Antar Pribadi dalam Kegiatan Imunisasi di Posyandu Desa Deunong Kec.Darul Imarah Aceh Besar - Khairuman; Dian Rahayu (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2024)
This community service activity is to provide services and insights into immunization. an effort to actively cause / increase a person's immunity to a disease so that if one day exposed to the disease will not get sick or only experience mild pain. Methods are theoretical and technical information that uses the discussion of progress in activities properly, especially important to express about the design of activities, data and / or tools used, as well as methods and stages of activities. This activity was moderated by the Deunong village midwife and facilitated by writers in community service activities who have experience and knowledge in their fields. The result of community service is that the Puskesmas Team provides briefings for the event. First, the National Child Immunization Month (BIAN) is given by the Puskesmas. Second, providing related materials (balanced diet, stop smoking, avoid stress, control blood pressure (regular exercise). Third, the content presented is tips to prevent stunting for pregnant women during the womb. The method of socialization activities uses the Interpersonal Communication Method (KAP) to change the behavior of cadres and the community for immunization awareness. Conclusion Socialization and mentoring activities related to Posyandu Deunong Village, Darul Imarah Sub-district and child immunization have a positive goal in increasing public awareness and participation in children's health. In this activity, the community is given an explanation of the benefits of Posyandu, the types of immunizations that are important for infants, and the consequences of not undergoing immunization regularly and continuously